2024
DOI: 10.3390/su16020735
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Spatial Dynamic Evolution of Digital Agriculture—Evidence from China

Jiajia Meng,
Baoyu Zhao,
Yuxiao Song
et al.

Abstract: Digital agriculture serves as a pivotal means of ushering in innovative agricultural practices and achieving sustainable agricultural development. Although agricultural digitalization has received increasing attention, the unbalanced development and regional disparities of digital agriculture are still key obstacles to sustainable agricultural development. Based on the data of 31 provinces in China from 2013 to 2021, this study evaluates the development level of digital agriculture in China, and further analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In addition, the transformation and upgrading of agricultural digitalization can fundamentally change the way farmers dispose of land and their management mode, and promote the reconstruction of modern rural industrial structures and the improvement of the marketization level of land factors. Some scholars have found that the digital economy can break the barriers of the market [11], promote the flow of factors, promote the digital management of land factors through digital technology [12], optimize the land management mode, and accelerate the transfer of rural land resources [13]. Through a data study of fixed observation points in rural regions, Gai et al [14] found that the degree of misallocation of agricultural land resources is increasing year by year, and land transfer can affect the allocation efficiency of land resources, while digital technology is the new kinetic energy to empower rural land transfer [15].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…In addition, the transformation and upgrading of agricultural digitalization can fundamentally change the way farmers dispose of land and their management mode, and promote the reconstruction of modern rural industrial structures and the improvement of the marketization level of land factors. Some scholars have found that the digital economy can break the barriers of the market [11], promote the flow of factors, promote the digital management of land factors through digital technology [12], optimize the land management mode, and accelerate the transfer of rural land resources [13]. Through a data study of fixed observation points in rural regions, Gai et al [14] found that the degree of misallocation of agricultural land resources is increasing year by year, and land transfer can affect the allocation efficiency of land resources, while digital technology is the new kinetic energy to empower rural land transfer [15].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…First of all, research on agricultural eco-efficiency primarily concentrates on measuring and analyzing the spatio-temporal evolution of agricultural eco-efficiency [8][9][10][11], the analysis of factors affecting agricultural eco-efficiency [12,13], and the study of paths to improve agricultural eco-efficiency [14,15]. Secondly, research on digital agriculture development mainly focuses on the measurement of the level of digital agriculture development in China and the analysis of regional differences [16,17], the paths and suggestions for digital agriculture development [18], and the exploration of mechanisms such as digital agriculture development boosting high-quality development and driving rural revitalization development [19][20][21][22]. Finally, in the exploration of the relationship between digital agriculture development and agricultural green development in rural areas, scholars generally agree that there is a significant correlation between them.…”
Section: Introductionmentioning
confidence: 99%